2021
DOI: 10.1101/gad.344531.120
|View full text |Cite
|
Sign up to set email alerts
|

The missing linker: emerging trends for H1 variant-specific functions

Abstract: Major advances in the chromatin and epigenetics fields have uncovered the importance of core histones, histone variants and their post-translational modifications (PTMs) in modulating chromatin structure. However, an acutely understudied related feature of chromatin structure is the role of linker histone H1. Previous assumptions of the functional redundancy of the 11 nonallelic H1 variants are contrasted by their strong evolutionary conservation, variability in their potential PTMs, and increased reports of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 102 publications
(303 reference statements)
1
31
0
Order By: Relevance
“…Thus, we extended this new type of HS-AFM analysis to another factor that is known to repress transcription. A prime candidate is the linker histone H1, which is known to efficiently compact H3 chromatin and restrict transcription (Clausell et al, 2009; Prendergast and Reinberg, 2021; Saha and Dalal, 2021). Previously we published HS-AFM movies of H3 chromatin and H3 chromatin with linker histone variant H1.5 (Melters and Dalal, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we extended this new type of HS-AFM analysis to another factor that is known to repress transcription. A prime candidate is the linker histone H1, which is known to efficiently compact H3 chromatin and restrict transcription (Clausell et al, 2009; Prendergast and Reinberg, 2021; Saha and Dalal, 2021). Previously we published HS-AFM movies of H3 chromatin and H3 chromatin with linker histone variant H1.5 (Melters and Dalal, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To which extent the latter could represent I compartments, similar to the ones described in activated B cells (29) remains to determined. Loss of H1 either in B or T lymphocytes was also shown to induce a profound reprogramming of epigenetic states with an expansion of H3K36me2 deposition at the expense of H3K27me3, suggesting that H1 binding plays an active role in balancing these modifications (203). Deletion of H1c and H1e in murine GC B cells conferred enhanced fitness and self-renewal, while at the molecular level inducing large-scale, but focal, chromatic decompaction and de-repression of stemness signature gene (202).…”
Section: Linker Histonesmentioning
confidence: 98%
“…Upon DNA damage, local changes to the condensation state of the chromatin are essential for the recruitment of the DNA damage repair factors. H1.2 has been shown to have a weaker ability to compact chromatin compared to most other variants, which endows H1.2 particular functions in DNA damage repair ( Orrego et al, 2007 ; Prendergast and Reinberg., 2021 ). It has been shown that ITCH mediated H1.2 K46 ubiquitination suppresses DNA damage repair by impairing RNF8/RNF168-dependent formation of 53BP1 foci, which is a crucial component of NHEJ (non-homologous end joining) signaling ( Chang et al, 2019 ).…”
Section: H12 and Dna Damage Repairmentioning
confidence: 99%